Pengaruh Rasio Liquiditas dan Solvabilitas Terhadap Profitabilitas Pada PT. Surya Baru di Jakarta - Rusnaeni, N; Lutfi, Asep Muhammad; Sari, Widya Intan (TIN: Terapan Informatika Nusantara, 2020)
This study aims to determine the effect of liquidity and solvency ratios on profitability at PT. Surya Baru in Jakarta. The method used is explanatory research with a sample of 8 years of financial reports. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, Current Ratio has a significant effect on Return on Assets of 46.5%, hypothesis testing obtained a significance of 0.042 <0.05. Debt to Asset Ratio has a significant effect on Return on Assets of 76.9%, hypothesis testing obtained a significance of 0.004 <0.05. Current Ratio and Debt to Asset Ratio simultaneously have a significant effect on Return on Assets of 82.4%, hypothesis testing obtained a significance of 0.013 <0.05.